Observation of photobleaching in Ge-deficient Ge16.8Se83.2 chalcogenide thin film with prolonged irradiation. Issue 1 (December 2017) - Zhang, Sen; Chen, Yimin; Wang, Rongping; Shen, Xiang; Dai, Shixun
Abstract We presented the unusual result of photobleaching (PB) in Ge-deficient Ge16.8 Se83.2 thin films with continuous irradiation with 560 nm laser for 12000 s, which is contradicted with the previous reports that the PB only occurs in Gex Se100-x films with x > 30. Observation of the dynamics variations of the photo-induced effects indicated that, photodarkening (PD) appears almost instantaneously upon light irradiation, saturates faster in a shorter time scale, and then photobleaching (PB) becomes dominant. Moreover, both PD and PB process accelerates with increasing irradiation power density. Raman spectra provided the evidence on the change of the photostructure of the samples, e.g. the structural transformation from Ge(Se1/2 )4 edge-sharing (ES) to corner-sharing (CS) tetrahedral and homopolar Ge-Ge and Se-Se bonds to heteropolar Ge-Se bonds.